2020
DOI: 10.3390/inorganics8120067
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of Sodium and Metforminium Decavanadates Decomposition and In Vitro Cytotoxicity and Insulin- Like Activity

Abstract: The kinetics of the decomposition of 0.5 and 1.0 mM sodium decavanadate (NaDeca) and metforminium decavanadate (MetfDeca) solutions were studied by 51V NMR in Dulbecco’s modified Eagle’s medium (DMEM) medium (pH 7.4) at 25 °C. The results showed that decomposition products are orthovanadate [H2VO4]− (V1) and metavanadate species like [H2V2O7]2− (V2), [V4O12]4− (V4) and [V5O15]5− (V5) for both compounds. The calculated half-life times of the decomposition reaction were 9 and 11 h for NaDeca and MetfDeca, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 71 publications
2
19
0
1
Order By: Relevance
“…It is very important to note that for the determination of the IC 50 values and the type of inhibition described above, the Metf-V 10 compound was added to the medium immediately before the beginning of the reaction being the rate measure within the next 2-3 min. The kinetics of the decomposition reaction of V 10 as well as of Metf-V 10 was previously determined by UV/Vis and 51 V NMR spectroscopy [45,66]. It was described that after addition of V 10 and/or Metf-V 10 in the medium, intact V 10 species with amounts of vanadate oligomers were detected [21,45,66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very important to note that for the determination of the IC 50 values and the type of inhibition described above, the Metf-V 10 compound was added to the medium immediately before the beginning of the reaction being the rate measure within the next 2-3 min. The kinetics of the decomposition reaction of V 10 as well as of Metf-V 10 was previously determined by UV/Vis and 51 V NMR spectroscopy [45,66]. It was described that after addition of V 10 and/or Metf-V 10 in the medium, intact V 10 species with amounts of vanadate oligomers were detected [21,45,66].…”
Section: Discussionmentioning
confidence: 99%
“…The Metf-V 10 crystals were solubilized in 10% dimethyl sulfoxide (DMSO) to a 5 mM stock concentration. Such vanadium compounds were previously characterized [40,[43][44][45].…”
Section: Preparation Of Decavanadate and Metformin-decavanadatementioning
confidence: 99%
“…Recently, a study reported the upregulation of hepatic AMPK levels and Akt cascade by a synergistic combination of metformin and bis(α-furancarboxylato)oxovanadium(IV) (BFOV) for the treatment of fatty liver disease [161]. Such reports of synergistic action of metformin and vanadium salts are not uncommon [162]. The most extensively studied vanadium compound in this context is vanadium(IV)chlorodipicolinate.…”
Section: Vanadium-mediated Ampk Activation-reduced Adipogenesismentioning
confidence: 99%
“…Decavanadate’s high negative charge allows it to interact with a wide range of molecules, including proteins, counterions, and lipid structures, influencing a variety of biological processes such as muscle contraction, calcium homeostasis, necrosis, actin polymerization, oxidative stress markers, and glucose uptake ( Aureliano, 2009 ). As a result, numerous compounds based on decavanadate and cationic organic ligands have been published in recent years, which have been shown to lower blood sugar levels ( Garcia-Vicente et al, 2007 ; Treviño et al, 2015 ; Treviño et al, 2018 ; Treviño and González-Vergara, 2019 ), induce neuronal and cognitive restoration mechanisms while treating metabolic syndrome ( Diaz et al, 2021 ), and inhibit the growth of protozoan parasites ( Li et al, 2010 ; Silva-Nolasco et al, 2020 ). The cytotoxic or differentiating activity of oxidovanadium complexes with organic ligands against various cancer cell types is well known ( Kioseoglou et al, 2015 ; Crans et al, 2018 ; Crans et al, 2019 ; Redher, 2020 ; Samart et al, 2020 ; Macedo Alves de Lima et al, 2021 ; Pessoa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, studying the cyclo-tetravanadate anion is critical because it will be the dominant species at physiological pH ( Sanchez-Lara et al, 2018 ). Anticancer properties of vanadium(V) anionic compounds have been discovered ( Cheng et al, 2018 ; Silva-Nolasco et al, 2020 ). Mg(H 2 O) 6 (C 4 N 2 H7) 4 V 10 O 28 •4H 2 O and (C 7 H 10 N) 4 [H 2 V 10 O 28 ]•2H 2 O were recently shown to have dose-dependent antiproliferative activity against human cancer cells U87, IGR39, and MDA-MB-231 ( Ksiksi et al, 2021 ; Louati et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%